Effect of Adding Commercial High Fiber Ingredients on Protein Quality of Casein and Gluten Diets for Rats as Assessed by Bioassays - Falcon Villa, Maria del Refugio; Hoyos, Jesus Manuel Barron (Pakistan Journal of Nutrition, 2016)
The food industry has responded to consumer demand for foods with higher fiber contents by developing products with high-fiber ingredients, which have unique properties that raise the fiber level. However, excessive consumption of high-fiber products can affect digestibility and protein quality. This study evaluated the effect of three commercial products used to increase fiber content in diets with casein or gluten as a protein source and Sprague Dawley rats as an experimental animal model. Six synthetic diets were prepared wherein three different fiber sources were added to a casein or gluten protein base: (i) insoluble fiber from wheat bran; (ii) soluble fiber with resistant maltodextrins and (iii) fiber from orange pulp that had similar amounts of soluble and insoluble fiber. Biological indicators such as weight were determined, as were the net protein ratio (NPR) and the percentage of apparent and true digestibility of nitrogen (AND, TND). Results were analyzed using statistical software with 95% significance. AND and TND of casein diets with high fiber ingredients ranged from 85.5 to 91.3% and from 87.8 to 94.21%, respectively. The gluten diets with different fiber sources had AND and TND that ranged from 87.8 to 90.4% and 91.1 to 93.8%, respectively. The NPR results ranged between 1.7 and 2.0. The results demonstrated that the addition of commercial fibers to gluten based diets resulted significant differences in digestibility and NPR.